Relationship between Metabolic Syndrome and Predictors for Clinical Benign Prostatic Hyperplasia Progression and International Prostate Symptom Score in Patients with Moderate to Severe Lower Urinary Tract Symptoms - Zhao, Sicong; Chen, Chao; Chen, Zongping; Xia, Ming; Tang, Jianchun; Shao, Sujun; Yan, Yong (Urology Journal, 2016)
Purpose: To investigate the association between metabolic syndrome (MetS) and the predictors of the progression of benign prostatic hyperplasia (BPH) and the corresponding frequency and severity of lower urinary tract symptoms (LUTS). Materials and Methods: A total of 530 men with moderate to severe International Prostate Symptom Score (IPSS) > 7 were recruited in the present study. The predictors for clinical BPH progression were defined as the total prostate volume (TPV) ≥ 31 cm3, prostate-specific antigen level (PSA) ≥ 1.6 ng/mL, maximal flow rate (Qmax) < 10.6 mL/s, postvoid residual urine volume (PVR) of ≥ 39 mL, and age 62 years or older. LUTS were defined according to the IPSS and MetS with the National Cholesterol Education Program-Adult Treatment Panel III guidelines. The Mantel-Haenszel extension test and the multivariate logistic regression analyses were used to statistically examine their relationships. Results: The percentage of subjects with ≥ 1 predictors for clinical BPH progression, the percentage of subjects with a TPV ≥ 31 cm3, the percentage of subjects with a PVR ≥ 39 mL, and the percentage of subjects with a Qmax < 10.6 mL/s increased significantly with the increasing in the number of MetS components (all P < .05). After adjusting for age and serum testosterone level, the MetS were independently associated with the presence of TPV ≥ 31 cm3 (OR = 17.030, 95% CI: 7.495-38.692). Moreover, MetS was positively associated with the severity of LUTS (P < .001) and voiding scores (P < .001), and each individual MetS component appeared as an independent risk factor for severe LUTS (IPSS > 19, all P < .001). Conclusion: Our data have shown that the MetS significantly associated with the predictors for clinical BPH progression and the frequency and severity of LUTS, especially the voiding symptoms. The prevention of such modifiable factors by promotion of dietary changes and regular physical activity practice may be of great importance for public health.